Interreligious Studies: Dispatches from an Emerging Field, edited by Hans Gustafson. Issue 1 (22nd July 2021) - Mirza, Younus
Abstract : Interreligious Studies: Dispatches from an Emerging Field, edited by Hans Gustafson. Baylor University Press, 2020. 295 pp., Hb., £35. ISBN 978-1481312547